If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + -3 = -6x + 3 Reorder the terms: -3 + 6y = -6x + 3 Reorder the terms: -3 + 6y = 3 + -6x Solving -3 + 6y = 3 + -6x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 6y = 3 + 3 + -6x Combine like terms: -3 + 3 = 0 0 + 6y = 3 + 3 + -6x 6y = 3 + 3 + -6x Combine like terms: 3 + 3 = 6 6y = 6 + -6x Divide each side by '6'. y = 1 + -1x Simplifying y = 1 + -1x
| (7/5)^-2 | | 5-x-2=3+4*4x+5 | | -36.812-(-4)+0.007= | | 30=10logx | | 3/8*(-2/-7)*3=0 | | -10=x+(24/x) | | -7.23+5.3= | | 6y=266-x | | 5-k-7+3k=k-5+k+3 | | 0.08(y-5)+0.16y=0.20-0.2 | | 34/5(17/5v-4/5)=-2159/25 | | 7ct^4-7cj^2=0 | | 3(2t-3)=6(t+3) | | y-55=146 | | 4.56-7.48= | | 0.14(y-1)+0.08=0.02y-1.8 | | 770/55*x=42 | | x/2=193 | | (4x/x^2-25)=(20/x^2-25)-(3/x-5) | | 282*3/x=47 | | 6x+3=5x+9-x | | 3x-64=-7 | | y=6/5x+2 | | 4+3r=5 | | y=y-b*x | | -19-21= | | Q^3-216Q=0 | | 9-(-23)= | | 3(x+1)/6=2x-1 | | x=8+2y | | -12x+2(x-5)+9=3x-10 | | 25/8+35/6 |